Sensitive system for visualising biotinylated DNA probes hybridised in situ: rapid sex determination of intact cells. - Burns, J (1985)
A fast and sensitive method for detecting biotinylated deoxyribonucleic acid (DNA) probes was used for sex determination of cells and tissues by in situ hybridisation of a probe "specific" for the Y chromosome (pHY 2.1). Within 24 hours this procedure visualizes the Y chromosome in fetal and adult cells and tissue, without background noise. This procedure should facilitate antenatal determination of sex on small numbers of uncultured cells. The sensitivity of the procedure also permits the chromosomal assignment of genes present in low copy number.